Indentation characteristics of rapidly solidified Al-Cu-V And Al-Cu-Ti alloys - Mandal R.K.; Mandal A.; Misra D.K.; Tiwari R.S.; Srivastava O.N. (My University, 2025)
We report indentation characteristics of metallic glasses and nano-composites in Al-Cu-V as well as in Al-Cu-Ti systems. The melt spun ribbons of these alloys are employed to study the surface hardness characteristics of the specimen containing microstructural features at various length scales. The characterization of these materials has been done with the help of transmission electron microscope, scanning electron microscope and X-ray diffractometer. The surface hardness characteristics of melt spun ribbons with and without crystallization have been studied using a micro-hardness tester. We shall discuss the indentation behavior of ribbons in relation to their structures and microstructures.